Complexity of Sentence Structure in Harry Potter and the Philosopher's Stone and Harry Potter and the Deathly Hallows - Růžičková, Martina (Univerzita Pardubice, 2019)
This diploma thesis is dedicated to the complexity of sentence structure in the first and seventh volume of Harry Potter series and further comparison of them with regards to the age of targeted readership. The first chapters of theoretical part cover the description of the term clause and further division of said term into main, superordinate and subordinate clause, followed by chapters studying functions of subordinate clauses and the finitness. Last chapters of theoretical part focus on the term sentence and its categorization. The theoretical part is followed by introduction of both analysed books and the genre and subsequently the quantitative and qualitative analysis is carried out comparing the findings for each category and drawing the conclusion whether the last volume is more complex than the first book.
Komplexnost větné stavby ve dvou dílech: Harry Potter a kámen mudrců a relikvie smrti
Keywords: clause; sentence; compound sentence; complex sentence; subordination; Harry Potter; klauze; souvětí; souvětí souřadné; souvětí podřadné; podřízenost